GET YOUR REAL ESTATE ACTIVITY IN ORDER IMPROVEMENT BASED ON FOREIGN EXPERIENCE - Kupaysinova Laziza Karimovna (American Journals, 2024)
This article analyzes foreign experience in regulating real estate activities. Three types of models are proposed to identify the strengths and weaknesses of real estate regulation in a number of countries: hard, medium and soft. According to the author's conclusion, based on the analysis data obtained from a number of countries, the most effective model of regulation of real estate activity is considered to be a strict model, which ensures a high level of the quality of services provided due to high requirements and regulation by the state and the professional community.
Keywords: Real estate, real estate market, real estate disposal, residential and non-residential premises, real estate activity, realtor, real estate regulatory model, real estate, agent.